Protecting patient information : a decision-maker's guide to risk, prevention, and damage control - Cerrato, Paul (Syngress is an imprint of Elsevier, 2016)
This book demonstrates how to conduct an in-depth analysis of a healthcare organization's information risk level, offers specific measures for lowering the risk of a data breach, and outlines the steps necessary when an organization experiences a data breach, even when it has taken all the right precautions.